2012
DOI: 10.5539/ass.v8n16p174
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture Studio of Universiti Kebangsaan Malaysia (UKM): Has the Indoor Environmental Quality Standard Been Achieved?

Abstract: Studio-based learning is a shared learning environment in which ambiguous problems are addressed. This paper primarily focused on the lightings at the Universiti Kebangsaan Malaysia (UKM)’s architecture studio and to find out whether it had achieved the Indoor Environmental Quality (IEQ). A good design, involving a space in a building, requires sufficient daylight in order to perform a task. This can be achieved by providing enough means to let in diffused light from the sky, yet keeping out direct light from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The green corridors create a Green Network, which helps people relink with nature and provides instant and societal welfare (Che-Ani et al, 2012;Plantation and Pasoh, 2014). Green corridors are beneficial to the quality of life because they bring elements of nature into the urban environment and stimulate the senses through the use of sound, color, motion, and smell in relatively positive ways (Moreno et al, 2020).…”
Section: Conceptual Background Of Green Corridorsmentioning
confidence: 99%
“…The green corridors create a Green Network, which helps people relink with nature and provides instant and societal welfare (Che-Ani et al, 2012;Plantation and Pasoh, 2014). Green corridors are beneficial to the quality of life because they bring elements of nature into the urban environment and stimulate the senses through the use of sound, color, motion, and smell in relatively positive ways (Moreno et al, 2020).…”
Section: Conceptual Background Of Green Corridorsmentioning
confidence: 99%
“…Spending more than 80% of peoples’ time indoors reveals the importance of IAQ on the health and comfort of occupants [ 78 ]. Studies have shown that low IAQ decreases the work performance of occupants [ 79 , 80 , 81 ].…”
Section: Environment and Society (Thermal Comfort And Iaq)mentioning
confidence: 99%
“…As a matter of fact, most studio studies are usually conducted outside of Malaysia. What we do know about this subject in the context of Malaysia is frequently confined to the studies of indoor environmental quality (Che-Ani, Tawil, Musa, Yahaya, & Tahir, 2012;Mirrahimi, Ibrahim, & Surat, 2012;Nasir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%